2019
DOI: 10.1136/bmjopen-2019-031369
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of potentially preventable medication-related hospitalisation indicators for Indigenous populations in Australia using a modified Delphi technique

Abstract: ObjectivesOne of the outcomes of a medication review service is to identify and manage medication-related problems (MRPs). The most serious MRPs may result in hospitalisation, which could be preventable if appropriate processes of care were adopted. The aim of this study was to update and adapt a previously published set of clinical indicators for use in assessing the effectiveness of a medication review service tailored to meet the needs of Indigenous people, who experience some of the worst health outcomes o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Even though some studies have reported high numbers of readmissions among home-dwelling older patients for a variety of drugs,38 this health issue was mostly investigated using prospective or cross-sectional studies with small samples. More insight is needed into the patterns of drug-related hospital readmissions and risk factors in order to design better interventions for addressing ADEs 39 40.…”
Section: Introductionmentioning
confidence: 99%
“…Even though some studies have reported high numbers of readmissions among home-dwelling older patients for a variety of drugs,38 this health issue was mostly investigated using prospective or cross-sectional studies with small samples. More insight is needed into the patterns of drug-related hospital readmissions and risk factors in order to design better interventions for addressing ADEs 39 40.…”
Section: Introductionmentioning
confidence: 99%
“…The 48 included studies which reported at least one opioid-related prescribing indicator (2, 9, 2469) were published during the period 2010-2019 (n=24)(13, 27, 28, 3033, 35, 3739, 41, 43, 45, 46, 49, 50, 54, 55, 57, 60, 63, 65, 66) followed by 2000-2009 (n=13) (9, 24, 29, 34, 42, 44, 48, 56, 58, 59, 62, 67, 68) and 2020-2022 (n=10) (2, 25, 26, 36, 40, 5153, 61, 69) and only one published in 1990-1999 (47) (Table 2). .…”
Section: Resultsmentioning
confidence: 99%
“…The incidence or prevalence of clinical indicators based on our findings in earlier studies 19‐21 were estimated using a tranche of Data for Decisions [Patron] data (Supporting Information, part 2) 22 . Further criteria for selecting clinical indicators were prevalence rates, the possibility of incorrect diagnoses, the availability of interventions that could be undertaken by qualified pharmacists and general practitioners, and other practical considerations.…”
Section: Methodsmentioning
confidence: 99%